2003
DOI: 10.1016/s0014-5793(03)00910-4
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion forces measured between a calcium blocker drug and its receptor in living cells using atomic force microscope

Abstract: The adhesion force between the tip of an atomic force microscope cantilever derivatized with nimodipine (a calcium blocker, from the dihydropyridine class, currently used in clinical medicine for hypertension) and living cells of Saccharomyces cerevisiae (unicellular eukaryotes which portray ultrastructural features characteristic of higher eukaryotic cells) was measured. This methodology allowed us to locate (and visualize) pores on the cell surface which may be responsible for calcium transportation in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is admitted that yeasts exchange this divalent cation outward. 6,10,13 However, Ahimou et al 44 concluded that the electrostatic surface distribution is heterogeneous for pH less than 6, corresponding to this study. Considering their results and AFM accuracy, this conclusion is carefully written but can be discussed at the nanometer length scales.…”
Section: Dlvo and Xdlvo Profilesmentioning
confidence: 49%
See 2 more Smart Citations
“…It is admitted that yeasts exchange this divalent cation outward. 6,10,13 However, Ahimou et al 44 concluded that the electrostatic surface distribution is heterogeneous for pH less than 6, corresponding to this study. Considering their results and AFM accuracy, this conclusion is carefully written but can be discussed at the nanometer length scales.…”
Section: Dlvo and Xdlvo Profilesmentioning
confidence: 49%
“…Indeed, the yeasts are provided with ion channels allowing solute transport and notably Ca 2+ . 6,10,13 Divalent cation in the suspending medium can have considerable effect. By adding 3 mM of calcium in a 100 mM NaCl solution, the local counterion concentration of a negative-charged surface equals 5M of Na + and 7M of Ca 2+ .…”
Section: Dlvo and Xdlvo Profilesmentioning
confidence: 99%
See 1 more Smart Citation